Produção de fala – aspectos neuromotores - Andrade, Claudia Regina Furquim de; Dantas, Mara de Oliveira Rodrigues Luiz (Distúrbios da Comunicação, 2012)
Dronkers N.;Ogar J. Brain areas involved in speech production. Brain, jul. 2004; 127:1461-1462. Maassen B. Issues contrasting adult acquired versus developmental apraxia of speech. Semin Speech Lang, nov. 2002; 23(4):257-66. Review.